(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The main aim of this study was to determine the benefits of use of naturally available Fibre called SISAL fibre used as additive in Bituminous concrete. Bituminous Mixture In which all component were mixed, placed and compacted at High temperature is called as Hot Mix Asphalt. HMA grade is referred as Dense Grade mixture (DGM). Asphaltic concrete is also called Bituminous Concrete (BC). Pavements are vulnerable to cracks, potholes, distresses and permanent deformation. In this study, SISAL fiber used in bitumen mixtures to study the benefits of using natural fibers, Eco-friendly design. Standard Marshall mix design test and drain down test were carried out. The process of mixing and preparing aggregates,The grading was done according to the specifications of (ISMORTH).Various percentages of binder changed to (4.5% -5.5%) and the added fiber changed to (0.1% -0.7%) of total aggregate and dust as a filler. The optimal value for bitumen is determined using the Marshall method and was found (5%). Similarly, the optimum fiber content of bitumen concrete (BC) was found (0.3%). Samples of Bituminous concrete (BC) mix were made and run those for obcs and of cs, then run them in tests such as Marshall Stability and Drain Down test to evaluate the result of adding fiber to the bitumen mixture. The test results indicates that the modification of bitumen with sisal fiber is used as an additive for bitumen mix, the Blends help increase stability and durability, reduce air void and flow value. After all, it was found that the use of Sisal fiber as an additive improves the properties. Like Stability, strength, durability, reduce drain down of bituminous concrete (B.C).